Produksi Coconut Vinegar dari Limbah Air Kelapa dengan Model Fermentasi Cair Termodifikasi Sel Yeast Terimobilisasi Kalsium Alginat - Afifah, Dini Nur; Mulyadi, Abdul Haris; Fadhila, Hana Syifa; Hasanah, Yeti R.; Savitri, Puput Wahyu Nita (UM Purwokerto Press, 2023)
Coconut (Cocos Nucifera L) is one of the Indonesia’s plantations comodities. Unfortunately, the abundance of raw materials has not had a significant impact on the export market for coconut products, especially functional food products. Based on that issue, research with the aim to produce diversified product of coconut was conducted. The product developed in this research was coconut vinegar produced by fermentation process of coconut waste water via liquid fermentation pathway. To increase efficiency and reduce production costs, the fermentation process was carried out simultaneously. In order to increase the yeast resistance to acetic acid produced by acetic acid bacteria (BAA), the process modification was conducted by using yeast immobilized formed by the calcium alginate matrix. The research results show that the optimum BAA inoculation time was 24 hours after the bead yeast inoculation. The maximum bead yeast mass obtained in this study was 25% m/v. Fermentation that was carried out with the maximum time and bead mass was able to produce coconut vinegar with an acetic acid content of 5.1 g/L, an alcohol conversion of 22.73%. This work is licensed under a Creative Commons Attribution 4.0 International License